Stronger together: Strategies to protect local sovereignty, ecosystems, and place-based communities from the global fossil fuel trade. (June 2017) - Allen, Maggie; Bird, Stoney; Breslow, Sara; Dolšak, Nives
Abstract: In the Pacific Northwest, residents are mobilizing to prevent the coastal export of fossil fuels and protect unique ecosystems and place-based communities. This paper examines the diverse groups, largely from the Bellingham area, and how they succeeded in blocking construction of what was to be the largest coal-shipping port in North America, the Gateway Pacific Terminal (GPT). Tribes, environmental organizations, faith-based groups, and other citizen groups used a multitude of approaches to prevent development, both independently and in concert. This paper reviews the various ways in which the groups collaborated and supported one another to resist the neoliberalization of the coast and support local sovereignty, unique ecosystems, and place-based communities. Groups like Power Past Coal, Protect Whatcom, and Coal-Free Bellingham fought for important and protective changes and evidenced communitywide political support, but the sovereign rights of the Lummi Nation were the legal bar to constructing the coal terminal. Highlights: Indigenous and non-indigenous tactics to stop a fossil fuel terminal are studied. Legal power of Lummi Nation's sovereign rights key to stopping the terminal. Various groups united due to similar core policy beliefs. Movement highlights how indigenous and non-indigenous groups can overcome conflict to achieve same goal.